The effect of the inlet chamber and diffuser on the reverse aerodynamic performance of an axial flow fan - Václav Cyrus; Jan Cyrus (Acta Polytechnica, 2024)
Flow reversal in axial fans is usually carried out by changing the direction of rotation of the fan and rotating the stator vanes. The total pressure losses of selected inlet fan chambers were determined using CFD data for the normal and reverse flow conditions. These losses are 3.5 to 7.2 times greater for the normal flow increase due to the flow reversal in three chambers with the hub/tip ratio of 0.45 to 0.63. The operating points of two complete fans made up of the inlet chamber, the diffuser, and the axial stages A and B with different aerodynamic load were obtained using one-dimensional engineering calculation method. It uses the measured performance data relating to both fan stages. The calculated volumetric flow rate ratio for reverse and normal operation is 0.68 and 0.55, respectively, for the complete axial fan with the stages A and B. The acquired results are in accordance with the customers’ requirements.